Penguatan Peran Orang Tua Dalam Mendapingi Pendidikan Anak Usia Dini Di Masa Pandemi Covid-19 - Rachman, Sry Anita (Universitas Hamzanwadi, 2020)
AbstractNowadays, Education in family becomes an attention in COVID-19 pandemic. ParentÃ¢â‚¬â„¢s role is being tested in covid-19 pandemic that surge this country, still giving the early age right for education. Strengthening parentÃ¢â‚¬â„¢s role is needed to give understanding to early age about pandemic that being epidemics today, importance to stay at home in order to be save and not to be contracted and contract the virus. Besides need in education, there is another thing that parent must be pay attention that is health factor, need for childÃ¢â‚¬â„¢s food and drink, psychological serenity, childÃ¢â‚¬â„¢s comfortable when study and play at home.Â Through descriptive study approach with ten parent who have child age 4-6 years old as respondents through questionnaire and interview by applying protocol in new normal, got the results: 1. there were two of ten parent who can adapt with the role as educator for their children an able to make comfort when giving lesson to child at home. 2. two of ten parent are able to make good communication among father, mother and teacher at school while learning from home. 3. The ten parent are agree with online long distance learning for the sake of break of chain transmitting of covid-19.Â Â Â Â Â Â